2015
DOI: 10.1371/journal.pone.0125698
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Foot-and-Mouth Disease Virus Infection in the Nasopharynx of Cattle; Tissue-Specific Distribution and Local Cytokine Expression

Abstract: Tissues obtained post-mortem from cattle persistently infected with foot-and-mouth disease virus (FMDV) were analyzed to characterize the tissue-specific localization of FMDV and partial transcriptome profiles for selected immunoregulatory cytokines. Analysis of 28 distinct anatomic sites from 21 steers infected with FMDV serotype A, O or SAT2, had the highest prevalence of overall viral detection in the dorsal nasopharynx (80.95%) and dorsal soft palate (71.43%). FMDV was less frequently detected in laryngeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 65 publications
5
78
1
2
Order By: Relevance
“…This observation is consistent with a previous study from this laboratory (72) and the fact viral RNA can be detected in semen for variable periods of time after the cessation of infectious virus shedding (86,87). Similar findings have also been reported in the case of other persistent viral infections such as foot-and-mouth disease virus (FMDV) (88)(89)(90). However, it was consistently noted that stallions that had stopped shedding had reduced local inflammatory responses compared with those of animals that remained EAV carriers.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with a previous study from this laboratory (72) and the fact viral RNA can be detected in semen for variable periods of time after the cessation of infectious virus shedding (86,87). Similar findings have also been reported in the case of other persistent viral infections such as foot-and-mouth disease virus (FMDV) (88)(89)(90). However, it was consistently noted that stallions that had stopped shedding had reduced local inflammatory responses compared with those of animals that remained EAV carriers.…”
Section: Discussionsupporting
confidence: 93%
“…Foot‐and‐mouth disease virus can be isolated from oropharyngeal fluid (OPF) and nasopharyngeal tissues for an extended period from a substantial proportion of cattle following subclinical or clinical FMDV infection (Pacheco et al., ; Stenfeldt, Eschbaumer, et al., ). Such persistently infected animals from which virus can be isolated at least 28 days post‐infection are defined as “FMDV carriers.” The duration of this carrier state may vary from months to years (Hayer et al., ; Tenzin, Dekker, Vernooij, Bouma, & Stegeman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the dorsal soft palate and the dorsal nasopharynx (the floor and ceiling of the nasopharynx, respectively) is a site of unique FMDV-host tropism in adult cattle during the early [14, 15, 48] and persistent [46, 47, 49, 50] stages of FMD pathogenesis. Earlier works have demonstrated detection of viral RNA for up to two days after cessation of viremia in numerous tissues, but substantially longer duration of detection (up to 72 dpi) in pharyngeal tissues and lymph nodes [47, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Several works have contributed to the growing understanding of the unique tropism of FMDV for the bovine nasopharynx during the acute [14, 15, 48] and persistent phase [46, 47, 49, 50] of infection. Microscopic localization of FMDV antigen has been demonstrated within the superficial epithelium of the nasopharynx of cattle [14, 15, 46, 47]. Similarly, FMDV RNA has been localized in the basal layers of the epithelium of the dorsal soft palate and pharynx [50, 61].…”
Section: Discussionmentioning
confidence: 99%